2014
DOI: 10.1103/physreva.89.023622
|View full text |Cite
|
Sign up to set email alerts
|

Resonant dynamics of chromium condensates

Abstract: We numerically study the dynamics of a spinor chromium condensate in low magnetic fields. We show that the condensate evolution has a resonant character revealing rich structure of resonances similar to that already discussed in the case of alkali-atoms condensates. This indicates that dipolar resonances occur commonly in the systems of cold atoms. In fact, they have been already observed experimentally. We further simulate two recent experiments with chromium condensates, in which the threshold in spin relaxa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Higher spin states are reached through , with . At ultracold temperatures Bose enhancement favors processes that involve the condensate, but all-condensate transitions like those seen in 18 , 43 are ruled out by the Zeeman energy threshold. No condensates appear in components .…”
Section: Chromium: Condensate Assisted Dipolar Scattering To Higher Smentioning
confidence: 99%
See 3 more Smart Citations
“…Higher spin states are reached through , with . At ultracold temperatures Bose enhancement favors processes that involve the condensate, but all-condensate transitions like those seen in 18 , 43 are ruled out by the Zeeman energy threshold. No condensates appear in components .…”
Section: Chromium: Condensate Assisted Dipolar Scattering To Higher Smentioning
confidence: 99%
“…In the classical-field model the cloud is described by the seven-component spinor wave function with one component for each value of the spin projection along the direction of the applied magnetic field . It evolves according to the multicomponent Gross-Pitaevskii equation 43 : where the energy functional consists of three parts. The first one represents the single-particle term which includes the kinetic, potential , as well as Zeeman energies, in which .…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In gaseous rubidium, the Einstein-de Haas effect becomes possible only because there exist resonances that amplify the transfer of atoms between dif-ferent Zeeman components [9,17]. It has been recently shown that dipolar resonances occur in chromium condensates [18] as well.…”
mentioning
confidence: 99%